Theoretical investigation and design of two-photon fluorescent probes for visualizing β-galactosidase activity in living cells. Issue 75 (26th July 2016) - Zhang, Chun; Wang, Dan; Zhang, Li; Guo, Jing-Fu; Ren, Ai-Min
Abstract : The two-photon fluorescent probes show dual signal for β-gal bio-imaging. Abstract : As a marker enzyme, the underlying biological mechanisms of β-galactosidase (β-gal) and its role in senescence and aging still remain unknown. Two-photon (TP) fluorescence microscopy (TPFM) is a promising approach for detecting β-gal enzyme activity in living specimens. In the present study, we have firstly designed a series of novel naphthalene-based β-gal ratiometric TP fluorescent chromophores, and carried out quantum-chemical calculations on their structural and linear/nonlinear optical properties. We have thoroughly studied the effects of different biological bridge groups (quinoline, benzo[ d ]thiophene, thiophene, diazine) and cyano groups on the one-photon absorption (OPA), fluorescence, as well as two-photon absorption (TPA) properties of β-gal probes and the corresponding reaction products. The calculated results show that the product molecules always exhibit longer absorption and emission wavelengths, and possess both stronger TP transition probability and a larger net charge change relative to that of corresponding β-gal probes, due to their better planarity and larger transition dipole moment. Our analysis suggests that the net charge change dominates the TPA cross section ( δ max ). There is an optimal match for δ max and radiation rate ( k r ) following the increase of the net charge change to improve nonlinear optical activity in the studied molecules. The substitution of benzo[ d ]thiazole with benzo[ d ]thiophene is an optimal approach for β-gal probe design with the largest fluorescence efficiency and δ max . We hope this contribution can provide detailed theoretical analysis of OPA and TPA properties of β-gal probes and relevant products, and provide insight into the structure–property relationships for guiding experimental design.